An ultrapotent human antibody neutralizes all maturation states of Zika virus - Bo Shu; Thiam-Seng Ng; Xin-Ni Lim; Shuijun Zhang; Victor A. Kostyuchenko; Guntur Fibriansah; Benjamin D. McElvany; Valerie Shyn-Yun Chew; Aravinda M. de Silva; Sean A. Diehl; Shee-Mei Lok (Proceedings of the National Academy of Sciences, 2025)
Zika virus (ZIKV), a flavivirus, causes a range of clinical complications including microcephaly in human fetuses. Currently, there is no treatment or vaccine. Different maturation states (mature and immature forms) of flavivirus particles have been observed to be released from infected cells and are infectious. To understand how an ultrapotent human antibody (HMAb) A9E can neutralize these Zika particles, we determined the cryoEM structures of the A9E Fab fragment complexed with mature (mZIKV) and immature (immZIKV) ZIKV to 2.8Å and 7.5Å, respectively. A9E binds to an epitope spanning Domain I (EDI), EDIII, and their linker in an E protein protomer in both immZIKV and mZIKV particles. A9E generally inhibited prior to or during virus attachment to cells, via virus aggregation, distortion of virus particles and inhibition of receptor binding. ImmZIKV is particularly sensitive to structural distortion by Fab A9E. The primary mode of infection used by ImmZIKV is via antibody-dependent enhancement of infection (ADE)—the formation of virus complex with nonneutralizing or subneutralizing concentrations of antibodies, that leads to enhanced infection of Fcγ positive myeloid cells. IgG A9E, by itself displays poor ADE activity. When IgG LALA mutant or Fab A9E is added to other enhancing antibody (DV62.5):virus complexes, they can strongly reduce the overall ADE activity. This is likely due to their ability to distort virus particle structure, suggesting that HMAb A9E could be a potential prophylactic and therapeutic candidate against all maturation states of ZIKV.